2019
DOI: 10.1002/aocs.12230
|View full text |Cite
|
Sign up to set email alerts
|

The Discrepancy of Fatty Acid Composition of Astaxanthin Esters and Total Fatty Acids in Photoautotrophic and Heterotrophic Chlorella zofingiensis

Abstract: Chlorella zofingiensis has great potential for astaxanthin and fatty acid production. This study investigated the accumulation of astaxanthin and total fatty acids (TFA), the fatty acid compositions of astaxanthin esters and TFA in photoautotrophic and heterotrophic C. zofingiensis, respectively. The results displayed that in photoautotrophic cells, 18:3 was the most predominant fatty acid, followed by 16:0, 18:2, and 18:1, while astaxanthin mono-esters (mono-AE) contained only 16:0 and 18:0, and astaxanthin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Heterotrophy allows maximum accumulation of lipids but lower levels of astaxanthin and lutein compared to mixotrophy and phototrophy [ 70 , 124 ]. The higher the glucose concentration the higher the lipid and TFA content in C. zofingiensis [ 74 , 151 ]. Araya et al [ 152 ] grew UTEX 32 phototrophically and found lipid productivity of only 10.95 mg/L/day, whereas Liu et al [ 74 ] obtained 660 mg/L/day and 710 mg/L/day with glucose and molasses respectively.…”
Section: Effect Of Culture Conditions Stress and Trophic Mode On Cell...mentioning
confidence: 99%
See 1 more Smart Citation
“…Heterotrophy allows maximum accumulation of lipids but lower levels of astaxanthin and lutein compared to mixotrophy and phototrophy [ 70 , 124 ]. The higher the glucose concentration the higher the lipid and TFA content in C. zofingiensis [ 74 , 151 ]. Araya et al [ 152 ] grew UTEX 32 phototrophically and found lipid productivity of only 10.95 mg/L/day, whereas Liu et al [ 74 ] obtained 660 mg/L/day and 710 mg/L/day with glucose and molasses respectively.…”
Section: Effect Of Culture Conditions Stress and Trophic Mode On Cell...mentioning
confidence: 99%
“…The benefits of lipid accumulation by heterotrophic growth are further evidenced by Liu et al [ 112 ]. Fatty acids, especially C18:1, promoted the accumulation of astaxanthin esters and the fatty acid composition of astaxanthin esters was correlated with the TFAs [ 151 ]. C18:1 was promoted by higher sugar concentrations, whereas C18:3 was promoted by lower sugar concentrations [ 74 , 112 ].…”
Section: Effect Of Culture Conditions Stress and Trophic Mode On Cell...mentioning
confidence: 99%